Geração de valor e impacto no comprometimento nas relações entre empresas - Ieda Lima Pereira (2009)
This paper takes into account how important it is to offer value and maintain lasting commercial relations. It is thus based on two models in literature - Ulaga and Eggert (2006a); Ribeiro et al. (2009) and on constructs such as dependence, relationship value and commitment. It proposes including the strategic orientation construct (of the customercompany) when investigating obtaining commitment. Two models were prepared and tested by using structural equations. They show that although dependence and strategic orientation positively influence commitment, it is the model that uses relationship value as a mediatorthat better explains it. Based on the results achieved we suggest that other research should be carried out to overcome the limitations of the present study and offer greater consistency to the proposed model.